Specialist reports (Scottish Historical and Archaeological Internet Reports, 2025)
The excavation work has demonstrated that Tarbert Castle is a construction of King Robert I (1306–1329) showing that both the Inner Bailey and Outer Bailey were built at the same time and not the result of two separate building campaigns as previously thought. The excavation work showed that well-preserved medieval deposits survive across the site also confirming several important aspects of the construction and layout of the castle establishing the presence of two portcullis gates giving access into the Outer Bailey also shedding light on the corner tower at the southwest of the same enclosure. The excavation also located the remains of one medieval building along with medieval deposits lying on the ridge south of the main castle, these confirmed the presence of the medieval burgh previously postulated as being in this area. Intriguingly an early historic 7th–8th century date was recovered from a deposit sealed below the castle walls which raises the possibility of the site being the ‘Tairpirt Boittir’ (spelled in various ways) mentioned in the Irish annals.